Regrets only - Scott, Kieran, 1974- (Gallery Books, 2023)
"Paige Lancaster, single mom and prodigal daughter, has returned to the East Coast from her prestigious, well-paid job in LA, writing for the smartest detective series on television. Something terrible happened to her back in Hollywood. Okay, two terrible things, one featuring a misplaced tire iron -- and now she's broke and homeless and living with her widowed mother and eight year old daughter, Izzy, in her hometown of Piermont, Connecticut: land of safe streets, good public schools, and a kick-ass Parent Booster Association. Paige can make this work, she's sure of it. Her dad, may he rest in peace, was Piermont's beloved police chief before he died two years ago. All she needs to turn her life around is to buckle down and concentrate on getting a new writing gig. But first, she has to get Izzy to school on time -- the very same school that she herself attended, back in the day. That's Fail #1. Then she runs into John Anderson, the boy she loved in high school, now a wealthy hedge-funder, still as gorgeous as ever, and (shoot) very married -- to gorgeous blond PBA president Ainsley Anderson. Then she almost gets a traffic ticket from sexy blue-eyed police officer Dominic Ramos. And has a run-in with fellow parent Nina, a prim, self-righteous accountant (with an unaccountably sexy husband) who's convinced that someone is siphoning funds from the PBA account to the tune of tens of thousands of dollars. Queen Bee Ainsley doesn't believe for a moment that anyone is stealing anything from the PBA. Neither does her posse of fellow PBA moms -- Lanie, Dayna, and Bee -- even though they're thick as, well, thieves. They're so close they even sport matching necklaces. Paige is determined to win them over, though it's not going to be easy, But when she shows up at the annual Parents and Pinot fundraiser, held at Ainsley and John's dazzling mansion in the toniest part of Piermont, she's caught in a compromising (though not unpleasant) position with John, accidentally rips a jagged hole in the guest bathroom, overhears an incriminating conversation, and discovers that her purse has gone missing. And later that night, Ainsley turns up dead at the bottom of her driveway. Did she fall? Or was she pushed? Dominic, aka Hot Cop, asks Paige to look into things in an unofficial capacity. She's a parent at the school, after all, and could be a useful undercover informant. But she's only written about detectives, never actually been one. Still, Dominic does have such beautiful eyes. And doing a little sleuthing means she can spend more time with John. Could he really be capable of murder? Is Nina on to something with her suspicions? Is Lanie's wish to take over as PBA President just the goal of an ambitious mom, or something darker? What's with the matching necklaces? And will Paige's decidedly unsavory past in California catch up to her? On second thought, maybe there's a new television season in the cards for Paige after all"--